S37 Matrix metalloproteinases drive collagen degradation and leukocyte migration in human tuberculosis: clinical and cellular studies. (14th November 2013) - Sathyamoorthy, T; Friedland, JS; Tezera, L; Elkington, PT
Abstract : Introduction and Objectives: Tuberculosis (TB) causes disease worldwide and multi-drug resistance is rising. Matrix metalloproteinases (MMPs) cause immunopathological lung matrix destruction, which results in transmission, morbidity and mortality. We specifically investigated collagenases in TB, studying secreted MMP-1 and MMP-8, and membrane bound MMP-14. Methods: Plasma was prospectively collected from TB patients (n = 151), respiratory symptomatics (n = 109) and controls (n = 120). Plasma MMP concentrations were measured by Luminex bead array. Induced sputum MMP-14 mRNA from TB patients and controls was quantified by RT-PCR. MMP-14 expression in TB patient biopsies was studied by immunohistochemistry. Human monocytes were stimulated with Mycobacterium tuberculosis (Mtb) H37Rv or Conditioned Media from Mtb infected monocytes (CoMTb) and MMP-14 measured using flow cytometry. Fluorescent microscopy detected MMP-14 and monocyte driven fluorescent collagen degradation. Monocyte migration was measured by the agarose spot assay. Results: Plasma MMP-1 was elevated in TB (median 229pcg/ml) compared to controls (median 2pcg/ml; p<0.001). MMP-8 was increased in TB (median 8359pcg/ml) compared to both respiratory symptomatics (median 3547pcg/ml; p<0.001) and controls (median 3236pcg/ml; p<0.001), and discriminated TB from respiratory symptomatics with moderate predictive ability, with an area under the curve of 0.79 by receiver operating characteristic analysis. In induced sputum, MMP-14 mRNA (normalised to β-actin) was increased 3.3-fold in TB compared to controls (p<0.05) and mRNA levels positively correlated with the extent of lung infiltration on chest radiograph (r = 0.483; p<0.05). Macrophages of TB granulomas in patient biopsies stained strongly positive for MMP-14. Mtb increased monocyte MMP-14 surface expression 31.7-fold (p<0.05) and CoMTb 17.5-fold (p<0.01), secondary to increased mRNA. Mtb-infected monocytes degraded collagen, with co-localised MMP-14 surface expression. Monocytes migrated to the edge of CoMTb-impregnated agarose drops, expressing MMP-14 on migration. Inhibition of MMP-14 activity with a neutralising antibody, decreased Mtb driven collagen degradation by 73% (p< 0.001) and CoMTb driven monocyte migration by 44% (p<0.001). Inhibition of chemokine signalling using pertussis toxin reduced CoMTb driven MMP-14 surface expression by 35% (p<0.05). Discussion: Collagen destruction is critical to pathogenesis in pulmonary TB, and these data implicate three collagenases, MMP-1, -8 and -14, in causing immunopathology and regulating leukocyte migration. MMPs may represent novel diagnostic and therapeutic targets.